Multiband light-curve analysis of the 40.5-min period eclipsing double-degenerate binary SDSS J082239.54+304857.19. Issue 4 (18th November 2020) - Kosakowski, Alekzander; Kilic, Mukremin; Brown, Warren
ABSTRACT: We present the Apache Point Observatory BG40 broad-band and simultaneous Gemini r -band and i -band high-speed follow-up photometry observations and analysis of the 40.5-min period eclipsing detached double-degenerate binary SDSS J082239.54+304857.19. Our APO data spans over 318 d and includes 13 primary eclipses, from which we precisely measure the system's orbital period and improve the time of mid-eclipse measurement. We fit the light curves for each filter individually and show that this system contains a low-mass DA white dwarf with radius RA = 0.031 ± 0.006 R⊙ and a RB = 0.013 ± 0.005 R⊙ companion at an inclination of i = 87.7 ± 0.2 ○ . We use the best-fitting eclipsing light curve model to estimate the temperature of the secondary star as T eff = 5200 ± 100 K. Finally, while we do not record significant offsets to the expected time of mid-eclipse caused by the emission of gravitational waves with our 1-yr baseline, we show that a 3σ significant measurement of the orbital decay due to gravitational waves will be possible in 2023, at which point the eclipse will occur about 8  s earlier than expected.